Pengaruh Berbagai Jenis Media Tanam Terhadap Pertumbuhan dan Hasil Tanaman Selada (Lactuca Sativa L.) Varietas New Grand Rapid pada Hidroponik Sistem Wick - Violeta Ivanka; Muharam Muharam; Darso Sugiono (Jurnal Ilmiah Wahana Pendidikan, 2021)
Lettuce is one of the vegetable crops with good economic value and market prospects for cultivation. Judging from the high conversion of agricultural land, as a solution, the system hydroponic technique can be used Wick (axis system) by adding an additional mixture of organic growing media. The purpose of this study was to obtain the right combination of organic growing media to increase the growth and development of lettuce (Lactuca sativa L.) variety New Grand Rapid. This research was conducted from June 2021 to August 2021 in the Screen House of Padjadjaran University located in Hegarmanah, Jatinangor, Sumedang, West Java. This research is an experimental method, using a single factor randomized block design (RBD) with 10 treatments and 3 replications, the treatments consisted of A (Rockwool), B (Peat moss), C (Husk Charcoal), D (Cocopeat), E (Peat moss + Husk Charcoal 1:1), F (Peat moss + Husk Charcoal 1:2), G (Peat moss + Husk Charcoal 2:1), H (Peat Moss + Cocopeat 1:1), I (Peat Moss + Cocopeat 1:2), J (Peat Moss + Cocopeat 2:1). The effect on the treatment was analyzed using the F test at a significant 5% level, to find out the best treatment, it was continued with the Duncan Multiple Range Test (DMRT) at a 5% level. The results showed that the addition of a mixture of organic growing media had a significant effect on the growth and development of lettuce (Lactuca sativa L.). Treatment E (Peat moss + Husk Charcoal 1:1) gave the highest fresh weight yield on lettuce (Lactuca sativa L.) variety New Grand Rapid with an average of 155.32 grams.